Dividend Payout Policy and Global Financial Crisis: A Study on Malaysian Non-Financial Listed Companies - Chan, Tze-Haw; Boo, Hooi-Laing; Ali, Ruhani (Asian Journal of Business and Accounting, 2021)
ABSTRACT Manuscript type: Research paper Research aims: This paper examines the impact of the global financial crisis on Malaysia non-financial index firms’ dividend policies. Design/Methodology/Approach: This paper used panel data of 495 firm-year observations of Malaysian non-financial index firms from 2006 to 2016. Research findings: Our findings indicate that firms adjust their dividend policies during the pre-crisis and post-crisis periods; more profitable and larger firms are more likely to distribute their dividend payouts, whereas firms with higher leverage are more likely to omit their dividends. Moreover, dividend policies that will increase firms’ valuation are adopted in Malaysia. This is reflected in the signalling theory with evidence that higher profitability exerts a positive influence on firms’ propensity to increase and/or maintain dividends over different study periods, implying that markets attach a high valuation to firms that can pay, especially during the crisis period. We also find the role of catering theory and smoothing hypothesis lost relevance in both crisis and non-crisis periods. Thus, the catering theory and smoothing hypothesis were not supported in Malaysia. Theoretical contribution/Originality: This study investigates the impact of the global financial crisis on Malaysia non-financial index firms’ dividend policies. This paper suggestion can act as a catalyst to more comprehensive and detailed researches and studies on dividend policy in any economic landscapes. Practitioner/Policy implications: This paper may also guide companies on the structure and use of dividend distribution over the precrisis, during the crisis, and post-crisis periods. Research limitation/Implications: One limitation of the study is that the measures used for dividend payout determinants are only based on the theory investigated. These measures may not completely reflect all the payout determinants. Future research could address this limitation by employing other factors in the study of dividend policy such as inflation, economic growth, and corporate governance. Keywords: Dividend Policy, Global Financial Crisis, Catering Theory, Signalling Theory, Smoothing Theory, Dividend Payout Option JEL Classification: G01, G35, O16